2011
DOI: 10.1163/092430410x523962
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Evaluation and Self-Sensing of Single Micro-Carbon Fiber/CNF–Brittle-Cement Composites using Electro-Micromechanical Tests and Acoustic Emission

Abstract: Interfacial evaluation and self-sensing were investigated for single carbon fiber/carbon nanofiber (CNF)-brittle-cement composites by electro-micromechanical techniques and acoustic emission (AE) under cyclic loading/subsequent unloading. During the curing process, the volumetric resistivity decreased dramatically, during the initial stage, due to increased contact points between the cement matrix and the CNF. The apparent modulus and electrical contact resistivity of micro-carbon fiber/CNF-cement composites w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Self-sensing by electrical resistance measurement has been reported in cement-based materials that have been rendered electrically conductive by the use of electrically conductive admixtures, such as steel fibers [7,8], carbon fibers [9][10][11][12][13][14][15], carbon nanotubes [16][17][18][19][20][21][22][23][24][25][26][27][28], carbon nanofibers [29,30], graphite nanoplatelets [16,31] and carbon black [28,[32][33][34]. Without the conductive additive, the cement-based material tends to be too high in the electrical resistivity for the resistance of a large volume of a cement-based structure to be effectively measured.…”
Section: Self-sensingmentioning
confidence: 99%
“…Self-sensing by electrical resistance measurement has been reported in cement-based materials that have been rendered electrically conductive by the use of electrically conductive admixtures, such as steel fibers [7,8], carbon fibers [9][10][11][12][13][14][15], carbon nanotubes [16][17][18][19][20][21][22][23][24][25][26][27][28], carbon nanofibers [29,30], graphite nanoplatelets [16,31] and carbon black [28,[32][33][34]. Without the conductive additive, the cement-based material tends to be too high in the electrical resistivity for the resistance of a large volume of a cement-based structure to be effectively measured.…”
Section: Self-sensingmentioning
confidence: 99%
“…Hyperbolic quadric relationships between the tensile load and the electrical resistance have been reported [22][23][24]. It was observe to depend upon interfacial properties between CF and M A N U S C R I P T A C C E P T E D In the study reported here, unlikely conventional FBG sensor or strain gauge methods, ER measurements were used for detection of cracking and crack propagation during flexural loading of short CFRP cylinders (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…Fibers can be incorporated into the cemented matrix to overcome these shortcomings [7]. The development of new nanosized fibers that can act as bridges across cracks and voids has opened a new field for nanosized reinforcement in concrete [8]. Carbon nanotubes (CNTs) are considered as one of the most advantageous nanomaterials for reinforcement purposes.…”
Section: Introductionmentioning
confidence: 99%